Estimating the isotopic niche of males and females of false killer whales (Pseudorca crassidens) from Magellan Strait, Chile - Haro, Daniela; Riccialdelli, Luciana; Blank, Olivia; Matus, Ricardo; Sabat, Pablo (Marine Mammal Science)
Odontocete cetaceans, due to their size, abundance, and energetic requirements, consume large quantities of prey and may therefore have substantial influence on the structure and dynamics of ecosystems (Bowen 1997, Trites 2002). Studies on their trophic ecology are fundamental to understand the role and ecological niche of these organisms in marine food webs (Tollit et al. 2010). The false killer whale (Pseudorca crassidens) is a top predator inhabiting tropical and subtropical waters of both hemispheres (Jefferson et al. 1993), rarely recorded in cold waters at latitudes greater than 50° (Baird 2002). Fil: Haro, Daniela. Universidad de Chile. Facultad de Ciencias. Laboratorio de Ecofisiología Chile Fil: Riccialdelli, Luciana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Blank, Olivia. Clínica Veterinaria Timaukel; Chile Fil: Matus, Ricardo. Centro de Rehabilitación de Aves Leñadura; Chile Fil: Sabat, Pablo. Universidad de Chile. Facultad de Ciencias. Laboratorio de Ecofisiología; Chile